2012
DOI: 10.1371/journal.pone.0041602
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the α1-Adrenergic Receptor Cause Vascular Impairments in Rat Brain as Demonstrated by Magnetic Resonance Angiography

Abstract: BackgroundCirculating agonistic autoantibodies acting at G protein-coupled receptors have been associated with numerous sever pathologies in humans. Antibodies directed predominantly against the α1-adrenergig receptor were detected in patients suffering from widespread diseases such as hypertension and type 2 diabetes. Their deleterious action has been demonstrated for peripheral organs. We postulate that antibodies to the α1-adrenergig receptor are relevant pathomolecules in diseases of the central nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…Immunohistological analyses confirmed α 1 ‐AR antibody‐induced blood vessel deficiencies. These findings confirm the hypothesis that the α 1 ‐AR antibody has effects reaching beyond previously reported macrovascular impairments in the predominantly extracranial major draining vessels of the rat brain and leads to cerebral microvessel damage throughout the brain. This further underlines the suggested significance of this antibody in brain diseases linked to vasculature impairments, such as dementia.…”
Section: Discussionsupporting
confidence: 90%
“…Immunohistological analyses confirmed α 1 ‐AR antibody‐induced blood vessel deficiencies. These findings confirm the hypothesis that the α 1 ‐AR antibody has effects reaching beyond previously reported macrovascular impairments in the predominantly extracranial major draining vessels of the rat brain and leads to cerebral microvessel damage throughout the brain. This further underlines the suggested significance of this antibody in brain diseases linked to vasculature impairments, such as dementia.…”
Section: Discussionsupporting
confidence: 90%
“…Positive stimulating/agonistic TSH-receptor antibodies are one of the risk factors for developing worsening thyroid eye disease and a drug-like TSH-receptor antagonist inhibits thyrotropin receptor-mediated stimulation of cAMP production in Graves' orbital fibroblasts (Neumann et al, 2012). In analogy, agonistic autoantibodies directed at G protein-coupled receptors such as the TSH-receptor may cause many other (endocrine) disorders including cerebrovascular impairment, stroke, and dementia, as recently shown in a rat model with antibodies against the alpha1-adrenergic receptor (Karczewski et al, 2012). For patients with type 1 (autoimmune) diabetes, a recent proof-of-concept, randomized, controlled clinical trial showed stimulation of the host innate immune response by Bacillus–Calmette–Guerin (BCG) treatment or Epstein Barr virus infection which transiently modified the autoimmunity in these patients (Faustman et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…More recently, efforts have begun in Alzheimer's patients to giving young blood to older patients and the company Alkahest has designed a randomized, double‐blind, placebo‐controlled, cross‐over trial . Other investigators have identified the presence of specific antibodies, namely alpha 1 adrenergic receptor antibodies (Ab), associated with blood vessel damage in the brain . Grifols International S.A. is working on a trial of therapeutic plasma exchange and therapeutic albumin and immunoglobulin infusion .…”
Section: Apheresis: the Fountain Of Youth?mentioning
confidence: 99%